Perencanaan Sumber Daya Manusia dalam Pendidikan Masa Depan - Merentek, Theo Chanra; Sumual, Tinneke Evie; Usoh, Elni Jeini; Kampilong, Joni Kutu (El-Idare, 2023)
This study aims to determine the planning of human resources (HR) in future education. This type of research uses qualitative descriptive analysis and data collection in the form of literature studies. Therefore it is obtained from several references including articles, books, or other scientific works related to the topic of discussion. Based on research showing that the achievement of educational goals and objectives will depend on planning, which includes HR planning. There are several activities that can be carried out when planning resources for education, namely identifying school goals, defining school philosophy, vision and mission, reviewing initial data and information owned, choosing alternative solutions to achieve goals, identifying human and material resources, analyzing obstacles that may get in the way, find out the different stages in the planning process.